Evaluation of the NCCN guidelines using the RIGHT Statement and AGREE-II instrument: a cross-sectional review. Issue 6 (23rd March 2019) - Wayant, Cole; Cooper, Craig; Turner, D'Arcy; Vassar, Matt
Abstract : Introduction: Robust, clearly reported clinical practice guidelines (CPGs) are essential for evidence-based clinical practice. The Reporting Items for practice Guidelines in HealThcare (RIGHT) Statement and Appraisal of Guidelines for Research and Evaluation (AGREE) II instrument were published to improve the methodological and reporting quality in healthcare CPGs. Methods: We applied the RIGHT Statement checklist and AGREE-II instrument to 48 National Comprehensive Cancer Network (NCCN) guidelines. Our primary objective was to assess the adherence to RIGHT and AGREE-II items. Since neither RIGHT nor AGREE-II can judge the clinical usefulness of a guideline, our study is designed to only focus on the methodological and reporting quality of each guideline. Results: The NCCN guidelines demonstrated notable strengths and weaknesses. For example, RIGHT Statement items 19 (conflicts of interest), 7b (description of subgroups) and 13a (clear, precise recommendations) were fully reported in all guidelines. However, the guidelines inconsistently incorporated patient values and preferences and cost. Regarding the AGREE-II instrument, the NCCN guidelines scored highly on the domains 4 (clear, precise recommendations) and 6 (handling of conflicts of interest), but lowest on domain 2 (inclusion of all relevant stakeholders). Conclusions: In this investigation, we found that NCCN CPGs demonstrate key strengths and weaknesses with respect to the reporting of key items essential to CPGs. We recommend the continued use of NCCN guidelines and improvements to weaknesses in reporting and methods. Doing so serves to improve the evidence delivered to healthcare providers, thus potentially improving patient care.